ANALISIS NILAI TAMBAH DAN EVALUASI KELAYAKAN USAHA RAJANGAN TEMBAKAU SAMPORIS - Rini Purwatiningsih; Adi Ismanto (University of Jember, 2016)
In the district of Bondowoso, farmers are marketing of tobacco leaf production in rough chopped to obtain the added value of tobacco leaves, so that farmers' income is expected to be increased. This study aims to determine whether the chopped tobacco samporis have added value, determine whether production of chopped tobacco samporis profitable, knowing production, revenue and price of chopped tobacco samporis has exceeded the value of BEP Production, BEP revenue, and BEP prices. This research was using a survey method. The sampling is done by total sampling. Technic data analysis used added value analysis, analysis of R/C, production BEP, BEP revenue, and BEP price. Chopped tobacco samporis have added value. The ratio of added value for The lower leaves, The middle leaves and Top leaves: = 83.33%, 80.50%, 82%. and the profit rate = 82.3%, 80%, 82.2%. The farming of chopped tobacco ​​samporis is profitable and feasible to be developed. R/C ratio = 2.903757405, average of production = 2358.33 kg higher than BEP production = 52.08 Kg, average of revenue = Rp. 68117333.33 higher than the BEP revenue = Rp. 1450501.59, - and the average of price = Rp. 27 833/kg higher than the price BEP = Rp.9947/ Kg.